Changes in Cross-Sectional Area of the Median Nerve and Body Composition Parameters after Treatment of Acromegaly: 1 year Follow-Up - Ivana Ságová; Daniela Kantárová; Marián Mokáň; Peter Vaňuga (International Journal of Endocrinology)
Objective. Median neuropathy is a common manifestation of acromegaly, although its pathology is uncertain. Changes in levels of growth hormone (GH) and insulin-like growth factor I (IGF-I) and body composition are potential parameters in pathology of median neuropathy in acromegaly. We aimed to assess changes in the cross-sectional area (CSA) of the median nerve and body composition in newly diagnosed acromegalic patients 1 year after treatment and to determine their mutual relationships. Design. This prospective study included 30 patients with newly diagnosed acromegaly and 30 healthy controls matched for age, gender, and body mass index. Physical and laboratory examinations, dual-energy X-ray absorptiometry (DXA), and ultrasound evaluations were performed at baseline and 1 year after initial treatment. Results. The CSA of the median nerve was increased in acromegalic patients compared with controls (13.1 mm2 [12.2–14.9] vs 7.5 mm2 [6.4–8.4], P<0.001). One year after treatment of acromegaly, GH and IGF-I levels decreased significantly. The median nerve CSA was significantly reduced after treatment (11.6 mm2 [10.2–13.1], P<0.001). Reduction of IGF-I levels correlated with a decrease in lean mass and increase in fat mass. The median nerve CSA positively correlated with IGF-I levels (R = 0.492, P=0.006) and lean mass (R = 0.419, P=0.021) in acromegalic patients before treatment. Conclusion. This study demonstrates a reduction in the median nerve CSA 1 year after treatment of acromegaly. These changes are closely associated with a reduction in IGF- I levels and in lean body mass. The enlargement of the median nerve in acromegaly can be reversed with adequate treatment.